Comparison of Repeated Task Oriented Training for the improvement of motor function with mirror Therapy and Conventional Treatment On upper limb in patients with stroke - A Randomized Controlled Trial (RCT) - Ruha Zulfiqar, M. Saddam Shoaib, Arooj Fatimah, Faiqa Mehmood Rana, Sania Maqbool, Kiran Safdar, Ainan Siddique, Ruhmah Amin, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: This study's goal is to illustrate how mirror treatment can be used with someone who has upper-extremity hemiparesis three months after suffering a cerebrovascular accident (stroke). These patients frequently fail to use their affected upper extremity to its full extent, possibly as a result of the "learned nonuse phenomenon. On each weekday of the 9-day intervention period, the patient performed tasks with the paretic upper extremity for 6 hours while being closely watched. Methods: Study population was patients from Mayo hospital Lahore. Study design was Randomized Controlled Trial. RCT:. 34 patients who met the requirements for inclusion were examined in this study. Before beginning any physical examination, each participant in this study gave their written, informed consent. Patients were divided equally into two groups. The Wolf Motor Function Test and the Numeric Pain Scale were used to measure pain and motor function on the first day. Group A received treatment using mirror therapy, whereas Group B received traditional care. Results: Mirror therapy was significantly effective in lowering pain and boosting functional activity in stroke patients, as evidenced by the comparison of the pre- and post-treatment scores on the NPRS and WMFT for groups A and B. Practical Implication: Stroke leads to multiple dysfunctions depending upon severity of lesion. It may decrease the range of motion and leads to functional dependency or disability. Physical therapy is important in the management of stroke including Strengthening, Stretching, ROMs and Manipulation and Mirror Therapy. This study provided an opportunity to share my personal experience with community. This study was conducted purely in clinical setting of Physiotherapy Department Mayo Hospital, Lahore. Conclusion: The study has proved that mirror therapy is more effective when combined with conventional treatment in management of stroke as compared to only use of conventional treatment. Keywords: Task oriented training, Motor function, Mirror therapy, conventional therapy, stroke, RCT